2013
DOI: 10.1002/mds.25678
|View full text |Cite
|
Sign up to set email alerts
|

The unified huntington's disease rating scale for advanced patients: Validation and follow‐up study

Abstract: The Unified Huntington's Disease Rating Scale (UHDRS) adequately measures decline in patients at early and moderate stages of Huntington's disease (HD). In patients with advanced HD, floor effects hamper the evaluation, thus calling for an adjusted scale. We designed the UHDRS-For Advanced Patients (UHDRS-FAP) to improve longitudinal assessment of patients at the advanced disease stage. Sixty-nine patients with a Total Functional Capacity score ≤ 5 were recruited in France and the Netherlands. Among them, 45 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Clinical examination of the oculomotor items of the UHDRS has its limitations due to difficulty in distinguishing between subtle possible pathology and normal eye movements, and due to interrater reliability. Previous studies have shown that the interrater reliability of the total UHDRS motor score is high, however they did not report the interrater reliability of the UHDRS oculomotor domain [ 3 , 19 ]. Additionally, eye movement abnormalities can have a nonspecific nature as well.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examination of the oculomotor items of the UHDRS has its limitations due to difficulty in distinguishing between subtle possible pathology and normal eye movements, and due to interrater reliability. Previous studies have shown that the interrater reliability of the total UHDRS motor score is high, however they did not report the interrater reliability of the UHDRS oculomotor domain [ 3 , 19 ]. Additionally, eye movement abnormalities can have a nonspecific nature as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, widely used HD rating scales e.g. UHDRS and UHDRS-FAP, and current treatment guidelines, do not address SD at all [8][9][10][11].…”
mentioning
confidence: 99%